Kekerasan Atas Nama Tuhan: Respons "Netizen" Indonesia - Fazlul Rahman (JURNAL INDO-ISLAMIKA, 2012)
Violence in the name of God—terrorism attacks, violence toward minority even inter religious conflicts—has nowadays become a global issue. In Indonesia, there are at least 30 cases of “holy” violence committed in the last ten years. The demand to have such freedoms, as of expression, of speech, of getting access to information, could be seen as a process of an ongoing democracy. Internet, in this context, is one of the popular media to channel this ambitions of democracy. On the other hand, many Muslim extremists use this change and this media to channel the ideology of jihad. This article aims to shed light on how the Indonesia netizen’s (cyber community) response to those kind of radical Islamist messages. By using descriptive content analysis to the comments of the respective issue in Kaskus website, this paper sees the variety of the responses that would contribute to the prevention of violence in the name of religion and suggest some solutions.